SPECIFICS OF THE EDUCATIONAL PROCESS AND ITS IMPACT ON THE FORMATION OF THE PERSONALITY OF YOUNG CHILDREN SCHOOL AGE IN CONDITIONS OF DEPRIVATION - Sivoplyas, N.V. (Pedagogy of Higher and Secondary Education, 2003)
No abstract.